THE SOCIAL SERVICE OF ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1950)
Accounting teachers can easily be so concerned to help their students grasp technicalities that they may miss the opportunity to drop suggestions now and then regarding the social service rendered by modern accounting. Business activities are such a prominent part of modern life that an elementary understanding of business, such as can be obtained through even a little study of accounting, can prepare the individual to be a more comprehending citizen. For example, business enterprises generate a very large amount of government revenue. Some understanding of enterprise accounting therefore provides some understanding of one of the bases on which modern government stands-government services paid for by revenue derived from business profits. Accounting not only gives us a glimpse of business as a generator of tax revenue but it helps us to realize that business, in one way or another, "is the paymaster of us all." Out of business activities comes wages of workers, wages of capital, wages of management. Business-by division of labor, by use of machine power, by developing mass distribution of products has created vast areas of employment for men and capital.